Neutrophil Lymphocyte Ratio, Platelet Lymphocyte Ratio and Mean Platelet Volume; which one is More Predictive in the Diagnosis of Pelvic Inflammatory Disease? - Kerem Doğa Seçkin; Mehmet Fatih Karslı; Burak Yücel; Burak Özköse; Doğukan Yıldırım; Berna Aslan Çetin; Halil Aslan (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: In the present study, we aimed to assess and compare the utility of complete blood count (CBC) parameters and C-reactive protein (CRP) in the diagnosis of pelvic inflammatory disease (PID).